2020
DOI: 10.1080/1059924x.2020.1834481
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Symptoms and Asthma among Fish Processing Workers

Abstract: After observing several clinical patients with respiratory symptoms, we initiated a questionnaire survey to assess prevalence of and predictors for asthma and work-related symptoms among workers in fish processing plants. A questionnaire with items on work conditions, work-related symptoms, and respiratory symptoms/diseases was sent to 916 fish processing workers, the 1836 licenced fishermen in Sweden, and 1965 controls; of those, 43%, 57%, and 53%, respectively, responded. Risks, hazard ratios (HRs), and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…while carrying out trimming process. Lack of PPE use can lead to increase the risk of contact with hazards which eventually leads to the increased cuts and burns severity (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…while carrying out trimming process. Lack of PPE use can lead to increase the risk of contact with hazards which eventually leads to the increased cuts and burns severity (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Crab, Anisakis simplex, red soft coral, and cuttlefish were the seafood most frequently responsible of OA. Dahlman-Höglund et al [15 ▪ ] reported that filters had a higher prevalence of OA compared to other fish processing workers and fisherman and their risk of OA increased during the years working in the industry [hazard ratio (HR) 3.6, 95% confidence interval (CI) 1.6–8.1]. Furthermore, the use of a pressure sprayer was identified as a risk factor for developing OA.…”
Section: Sensitizing Agentsmentioning
confidence: 99%
“…In the latter study, the risk of asthma among fish filleting workers increased with employment duration in fish processing and the use of pressured sprayers. Filleters were also more likely to change their work tasks due to respiratory symptoms than other fish processing workers [32]. Mason et al used data from the Surveillance of Work-related and Occupational Respiratory Disease reporting system for 1992-2017 showing an excess incidence of annual OA for UK land-based seafood processors of 70 per 100 000 workers compared to 2.9 in 'all other industries', implicating prawns and salmon/trout processing [33].…”
Section: Key Pointsmentioning
confidence: 99%